2010
DOI: 10.1371/journal.pone.0010078
|View full text |Cite
|
Sign up to set email alerts
|

Osmolytes Contribute to pH Homeostasis of Escherichia coli

Abstract: BackgroundCytoplasmic pH homeostasis in Escherichia coli includes numerous mechanisms involving pH-dependent catabolism and ion fluxes. An important contributor is transmembrane K+ flux, but the actual basis of K+ compensation for pH stress remains unclear. Osmoprotection could mediate the pH protection afforded by K+ and other osmolytes.Methods and Principal FindingsThe cytoplasmic pH of E. coli K-12 strains was measured by GFPmut3 fluorimetry. The wild-type strain Frag1 was exposed to rapid external acidific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 35 publications
3
40
3
Order By: Relevance
“…Each of the K ϩ transport systems Trk1, Trk2, GlnQHMP, and Kch was tested for its role in K ϩ uptake by complementing the E. coli strain TK2420 with these systems. E. coli TK2420 is a wellestablished model organism to characterize K ϩ transporters because of its lack of constitutive transporters and inability to transport K ϩ (31,(61)(62)(63). We observed that complementing E. coli TK2420 with Trk1, Trk2, or GlnQHMP facilitated significant K ϩ acquisition and enabled normal growth in low K ϩ concentrations and under stress conditions imposed by high salt concentrations and low pH.…”
Section: Discussionmentioning
confidence: 96%
“…Each of the K ϩ transport systems Trk1, Trk2, GlnQHMP, and Kch was tested for its role in K ϩ uptake by complementing the E. coli strain TK2420 with these systems. E. coli TK2420 is a wellestablished model organism to characterize K ϩ transporters because of its lack of constitutive transporters and inability to transport K ϩ (31,(61)(62)(63). We observed that complementing E. coli TK2420 with Trk1, Trk2, or GlnQHMP facilitated significant K ϩ acquisition and enabled normal growth in low K ϩ concentrations and under stress conditions imposed by high salt concentrations and low pH.…”
Section: Discussionmentioning
confidence: 96%
“…5 and 6). Each of these agents is capable of imposing increased osmotic pressure on bacteria (28)(29)(30). One interpretation of this surprising result is that YqjA may additionally possess osmosensing capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the absence of potassium resulted in a greater response with 75 statistically different RNA transcript ratios (Figs 3 and 4a and Supplemental Files 4 and 5). A sodium/proline symporter (Saci_0383) increased RNA transcripts in the absence of sodium, likely due to its role in cation homeostasis (Kitko et al, 2010). Increased RNA transcripts were observed for the subunit D of archaeal succinate dehydrogenase (Saci_0979) in the absence of sodium, while RNA transcripts for the cytochrome b homologue (soxC) of the Sox-ABCD complex (Saci_2087) increased under full salt.…”
Section: Rna Transcripts As a Response To Removal Of Either Potassiummentioning
confidence: 99%